Remedies and obligations imposed by competition authorities - Marcos, Francisco (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
Aimed at ending the infringements and restoring the free market competitive conditions there are other corrective remedies different to fines that the European Commission, the National Markets and Competition Commission (NMCC) and the Spanish regional competition authorities can impose when a violation of the prohibitions of anticompetitive behavior has been found. This paper conducts a survey of these remedies, which inspired in the reestablishment of legality, the elimination of the distortions to competition and in the prevention of future anticompetitive actions, may be adopted by competition authorities. Aside from ceasing orders of the forbidden conducts, which paralyze them and re-establish the legal order, there are other remedies aimed at restoring free competition in the market, removing the effects of anticompetitive conducts and preventing them from happening again in the future. This paper examines the wide variety of obligations that have been adopted as remedies by competition authorities and the problems they have raised in practice.